·
·
¡Hola Francisco!
Vamos a ver si es verdad
$$\begin{align}&h(x)= \sqrt{x^2-4},\\&r(x)= \sqrt{x^2+4}, \\&\text{demuestra que }\\&h\left(n+\frac 1n\right) + r \left(n - \frac 1n\right)= 2n\\&\\&h\left(n+\frac 1n\right) + r \left(n - \frac 1n\right)=\\&\\&\sqrt{\left(n+\frac 1n \right)^2-4}+\sqrt{\left(n-\frac 1n \right)^2+4}=\\&\\&\sqrt{\left(\frac {n^2+1}n \right)^2-4}+\sqrt{\left(\frac {n^2-1}n \right)^2+4}=\\&\\&\sqrt{\frac {(n^2+1)^2}{n^2}-4}+\sqrt{\frac {(n^2-1)^2}{n^2}+4}=\\&\\&\sqrt{\frac {(n^2+1)^2-4n^2}{n^2}}+\sqrt{\frac {(n^2-1)^2+4n^2}{n^2}}=\\&\\&\frac{\sqrt{(n^2+1)^2-4n^2}}{n}+\frac{\sqrt{(n^2-1)^2+4n^2}}{n}=\\&\\&\frac{\sqrt{n^4+2n^2+1-4n^2}}{n}+\frac{\sqrt{n^4-2n^2+1+4n^2}}{n}=\\&\\&\frac{\sqrt{n^4-2n^2+1}}{n}+\frac{\sqrt{n^4+2n^2+1}}{n}=\\&\\&\frac{\sqrt{(n^2-1)^2}}{n}+\frac{\sqrt{(n^2+1)^2}}{n}=\\&\\&\frac{n^2-1}{n}+\frac{n^2+1}{n}=\frac{2n^2}{n}=2n\\&\\&\\&\\&\\&\\&\\&\\&\end{align}$$
Luego era verdad. Y eso es todo, espero que te sirva y lo hayas entendido.
Saludos.
;
: